Relationships and disputes between history and restoration during the patrimonialization process of the colonial architecture in Argentina (1937-1947). Opposed views inside the national comission of museums, monuments and historical sites - Herr, Carola I. (2023)
The present work exposes the foundational period of heritage management in Argentina (1937-1947) inquiring into the relations, crosses, displacements and conflict of interest between history and architectural restoration. At local level, heritage awareness and the creation of a specific institution to safeguard the national values was conceived and represented by historians. Nevertheless, the National Commission of Museums, Monuments and Historical Sites soon required the incorporation of an architect to start the restoration works. Since then, approaches, perspectives and roles from different disciplines get crossed. Two theoretical and methodological strategies were used for the development of this work: professional profiles of the Commission; different sources of information exposing the relationship between history and restoration were analyzed.